Assembly, structures, electrocatalytic and photocatalytic properties of a series of Anderson-type polyoxometalate-based metal–organic complexes based on flexible pyridyl-amide ligands. (9th March 2017) - Wang, Xiu-Li; Sun, Junjun; Lin, Hongyan; Chang, Zhihan; Bai, Xue; Wang, Xiang
Graphical abstract: Five new Anderson-type polyoxometalate-based metal–organic complexes with various networks constructed from different bis-pyridyl-bis-amide ligands have been prepared and characterized. The electrochemical behaviors and the photocatalytic activities have been described. Abstract: Five new Anderson-type polyoxometalate-based metal–organic complexes, [Cu4 (μ3 -OH)2 (H2 O)6 (4-dpye)2 (TeMo6 O24 )]·2H2 O (1 ), [Cu(4-dpyb)(CrMo6 (OH)6 O18 )2 (H2 O)2 ][Cu(4-dpyb)(H2 O)4 ](4-H2 dpyb)·6H2 O (2 ), H[Cu2 (3-dpyb)2 (C2 O4 )(CrMo6 (OH)6 O18 )]·8H2 O (3 ), [Cu2 (4-dpyh)(CrMo6 (OH)5 O19 )(H2 O)8 ]·10H2 O (4 ) and [Cu4 (μ2 -OH)(μ3 -OH)(H2 O)6 (4-dpyh)(TeMo6 O24 )]·H2 O (5 ) (4-dpye = N, N′-bis(4-pyridinecarboxamide)-1, 2-ethane, 4-dpyb = N, N′-bis(4-pyridinecarboxamide)-1, 4-butane, 3-dpyb = N, N′-bis(3-pyridinecarboxamide)-1, 4-butane, 4-dpyh = N, N′-bis(4-pyridinecarboxamide)-1, 6-hexane), were hydrothermally prepared and structurally characterized by single crystal X-ray diffraction analyses and characterized by single-crystal X-ray diffraction, elemental analysis, IR, powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA). Complex1 is a 2D network, which is constructed from Cu4 –TeMo6 inorganic chains and 4-dpye ligands. Complex2 contains two types of 1D chains. Complex3 shows a 1D ring-like chain structure, in which the CrMo6 anions act as fourfold monodentate ligands consolidating the [Cu2 (3-dpyb)2 (C2 O4 )] rings. Complex4 is a 0D structure containing a dinuclear complex cation [Cu2 (4-dpyh)] 4+ and discrete CrMo6 anion. Complex5 exhibits a 3D framework constructed from 2D Cu4 –TeMo6 inorganic layer and 4-dpyh ligands. The spacer lengths and N-donor sites of the bis-pyridyl-bis-amide ligands, as well as different polyoxometalates play important roles in tuning the structures of the title complexes. The electrochemical behavior and electrocatalytic properties, as well as the photocatalytic activities of the title complexes have been studied.